Optimization of power and efficiency of a vortex water turbine through blade–outlet distance and transmission ratio analysis - Asagi, Florensius Kitaro; Wijayanto, Danar Susilo; Saputra, Taufik Wisnu (Politeknik Negeri Lhokseumawe, 2026)
As fossil fuel resources decline, vortex water turbines offer a promising renewable energy alternative by utilizing river flow. This experimental research aims to analyze the effect of blade distance from the outlet and transmission ratio on the electrical power and efficiency produced by vortex water turbines as a renewable energy solution. Three variations of blade distance from the outlet (20 mm, 40 mm, and 60 mm) and three variations of transmission ratio (1:3, 1:4, and 1:5) were tested under seven water flow rate variations of 27.8 l/min, 33.68 l/min, 34.11 l/min, 34.54 l/min, 34.97 l/min, 35.4 l/min, and 35.83 l/min. Data were collected for 5 minutes, with a 10-second interval for each parameter. Test results show that the highest electrical power of 4.88 watts was achieved at a blade distance of 20 mm from the outlet, a transmission ratio of 1:5, and a water flow rate of 35.83 l/min. Meanwhile, the highest turbine efficiency of 11.25% was obtained at a blade distance of 20 mm from the outlet, a transmission ratio of 1:3, and a water flow rate of 35.83 l/min. Increasing blade–outlet distance reduced both power and efficiency, while higher transmission ratios increased power but decreased efficiency due to torque–speed trade-offs. These results confirm that the distance between the blade and the outlet, and the transmission ratio, are critical parameters for optimizing performance of vortex turbines. A blade distance closer to the outlet provides the best performance and a larger transmission ratio will also improve performance, although transmission loading must also be considered.